Effect of waste materials on acoustical properties of semi-dense asphalt mixtures. (January 2022) - Poulikakos, L.D.; Athari, S.; Mikhailenko, P.; Kakar, MR.; Bueno, M.; Piao, Z.; Pieren, R.; Heutschi, K.
Graphical abstract: Abstract: Among the urban societal burdens rolling noise generation from tire pavement interaction and urban waste stand apart. Many urban waste materials can be used in pavements with comparable mechanical performance. Noise-related pavement characteristics such as porosity, sound absorption and surface texture, were measured for semi-dense low noise pavement mixtures using urban waste materials namely: recycled concrete aggregates, crumb rubber, polyethylene terephthalate and polyethylene. The results show that the use of these materials is a viable sustainable option for low noise pavements, however that may affect the noise reduction properties. With values around 0.2 at 1000 Hz, the sound absorption of all the mixtures is relatively low and the use of mean profile depth (MPD) alone is not enough to characterize the noise reduction properties. Surface texture was altered in different degrees depending on the waste material used. The results presented can aid in policy pertaining to noise abatement and waste reduction.